2021
DOI: 10.1002/adma.202100793
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Chemical Lithiation Transforms Diamond‐Like Carbon into an Ultrastrong Ion Conductor for Dendrite‐Free Lithium‐Metal Anodes

Abstract: Lithium (Li)‐metal anodes are of great promise for next‐generation batteries due to their high theoretical capacity and low redox potential. However, Li‐dendrite growth during cycling imposes a tremendous safety concern on the practical application of Li‐metal anodes. Herein, an effective approach to suppress Li‐dendrite growth by coating a polypropylene (PP) separator with a thin layer of ultrastrong diamond‐like carbon (DLC) is reported. Theoretical calculations indicate that the DLC coating layer undergoes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(52 citation statements)
references
References 106 publications
(16 reference statements)
1
46
0
Order By: Relevance
“…Recent researches indicated that in situ lithiation or prelithiation is another approach to improve the lithiophilicity and Li-ion conductivity of carbon materials. [42,43] This is actually consistent with our observation that after the first Li deposition/striping cycle inside aCNTs-600, the following cycles were significantly accelerated and the nanotube appeared superlithiophilic (see Video S3). As for the aCNTs (especially carbonized at 1000 °C) failed to encapsulate Li in the initial cycle, the aslithiated shells can also gain improved lithiophilicity, which could result in the encapsulation of Li in the following cycles in some cases (see Figure S35; such pre-lithiation may need a few cycles).…”
Section: Resultssupporting
confidence: 90%
“…Recent researches indicated that in situ lithiation or prelithiation is another approach to improve the lithiophilicity and Li-ion conductivity of carbon materials. [42,43] This is actually consistent with our observation that after the first Li deposition/striping cycle inside aCNTs-600, the following cycles were significantly accelerated and the nanotube appeared superlithiophilic (see Video S3). As for the aCNTs (especially carbonized at 1000 °C) failed to encapsulate Li in the initial cycle, the aslithiated shells can also gain improved lithiophilicity, which could result in the encapsulation of Li in the following cycles in some cases (see Figure S35; such pre-lithiation may need a few cycles).…”
Section: Resultssupporting
confidence: 90%
“…S10†), the LiFePO 4 |PVDF–DBDPO/PP|Li cell demonstrates nonetheless an especially excellent performance with the specific capacity (113 mA h g −1 initially) and cycling stability (capacity retention of 100% after 1000 cycles) overwhelmingly superior to those of the LiFePO 4 |PP|Li cell (initial capacity of 98 mA h g −1 with the retention of 64.2%). Therefore, even when compared with the separators which are positively reported in the literature, 20,22,38,41,42,44,53,61–63 the LiFePO 4 /Li cell with the PVDF–DBDPO/PP separator still exhibits considerable competitive advantages (Fig. 7d), in not only the highly stable long-term cycling performance, but also the real demand of the lower-content liquid electrolyte (10 μL cm −2 ) for higher cell safety.…”
Section: Resultsmentioning
confidence: 83%
“…6–8 In this context, on the one hand, lots of efforts for safe LMBs commonly focus on exploring fire-prevention systems by introducing a fire retardant into electrolytes, 9,10 modifying separators with inorganic particles, 11,12 designing thermoresponsive switch membranes and so on. 13–15 On the other hand, the studies aspiring to achieve long cycling properties pay close attention to fresh strategies of electrolyte/electrode interface engineering for dendrite-free lithium anodes, such as in situ formation of an artificial SEI film, 16–18 construction of three-dimensional lithium matrices, 19 preparation of high-strength composite separators as mechanical barriers, 20,21 and interfacial redistribution of ions across the separators or at the lithium metal surface. 22–24 Both categories of these methods provide diversified perspectives for the progress of high-performance LMBs, while most of them only achieve high fire resistance or good lithium dendrite inhibition alone.…”
Section: Introductionmentioning
confidence: 99%
“…The parasitic reaction products were also visually negligible, as confirmed by detailed chemical analyses below. Although the suppression of the lithium dendrite by nano-porous separator have been reported 16 , 22 26 , inhibition the continuously occurred parasitic reaction between Li 0 and liquid electrolyte was firstly studied in this work.…”
Section: Resultsmentioning
confidence: 99%